Sinai trafficking: origin and definition of a new form of human trafficking - Reisen, Mirjam (2015)
The phenomenon that is coined "Sinai Trafficking" started in 2009 in the Sinai desert. It involves the abduction, extortion, sale, torture, sexual violation and killing of men, women and children. Migrants, of whom the vast majority are from Eritrean descent, are abducted and brought to the Sinai desert, where they are sold and resold, extorted for very high ransoms collected by mobile phone, while being brutally and "functionally" tortured to support the extortion. Many of them die in Sinai. Over the last five years broadcasting stations, human rights organisations and academics have reported on the practices in the Sinai and some of these reports have resulted in some confusion on the modus operandi. Based on empirical research by the authors and the analysis of data gathered in more than 200 recorded interviews with Sinai hostages and survivors on the practices, this article provides a definition of Sinai Trafficking. It argues that the term Sinai Trafficking can be used to diff